Knowledge, attitude and practice towards iron deficiency anaemia among pregnant women in Kota Kinabalu, Sabah - Nurul Asyiqin Iskandar; Bibi Nabihah Abdul Hakim; Siti Nur Hazwani Oslan; Norliza Julmohammad (Faculty of Food Science and Nutrition, UMS, 2025)
Introduction: Iron deficiency anaemia is a major public health concern, particularly among pregnant women, and it not only affects their health but also their birth outcomes. Despite the implementation of nutrition interventions and iron supplementation, the prevalence remains high. Therefore, this study aimed to determine the level of knowledge, attitude, and practice towards anaemia and its association with anaemia among pregnant women in Kota Kinabalu, Sabah. Methods: This cross-sectional study recruited 162 pregnant women aged 18 to 49 years who attended two randomly selected health clinic located in Kota Kinabalu, through convenient sampling. A Malay back-to-back translated questionnaire was used to determine the level of knowledge, attitude, and practice towards anaemia. Results: Most pregnant women (54.3%) had good knowledge and 51.2% showed a positive attitude towards anaemia. The pregnant women elicited moderate practice towards anaemia. A total of 37% of pregnant women were anaemia. No association was found between knowledge and attitude toward anaemia on the incidence of anaemia among pregnant women. Conclusion: This present study revealed that while most pregnant women had good knowledge and a positive attitude towards anaemia, their practices were only moderate. No association was found between knowledge and attitude and the incidence of anaemia. These findings warrant further in-depth study in a wider population of pregnant women to unravel the incongruities identified.